JOYFUL LEARNING DALAM MENINGKATKAN KEMAMPUAN ANALISIS SISWA PADA MATA PELAJARAN AKUNTANSI - Efni Cerya (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2016)
The main purpose of this study, researchers are as motivation for teachers in order to implement contextual learning approach and encourage students' interest because it uses a learning model that is attractive. Accounting is indeed one of rich analysis and mathematical subject and delivers its own challenges. Nevertheles, creating a joyfull and quality learning is the responsibility of a teacher. The creativity of a teacher will be able to reduce the saturation and difficulty student in learning. Create joyfull learning is one of the alternatives that can be applied by teachers in achieving this. Interesting and effective process that it will be able to achieve learning objectives in the cognitive, affective and psychomotor.